A preparation method of metallized molybdenum-manganese paste

By preparing molybdenum-manganese metallized paste, using multiple heat treatments and ball milling processes, the problem of insufficient bonding strength between metal film and ceramic matrix materials in the prior art is solved, and a metallized layer with high density and tensile strength is achieved.

CN119176727BActive Publication Date: 2025-03-14HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411675963.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The bonding force of the existing metal film made of sintered molybdenum-manganese paste with ceramic matrix material is generally, and there are obvious limitations.

Method used

By mixing molybdate, polymer microspheres, surfactant and ammonia water, drying after hydrothermal reaction, and undergoing multiple heat treatments, finally mixing ball mills with activator and manganese monoxide, adding organic binder to prepare a molybdenum-manganese paste.

Benefits of technology

The prepared metallized layer has high density, continuous skeleton, excellent conductivity, and does not easily appear agglomeration or pores during the firing process, which improves the uniformity and tensile strength of the microstructure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176727B_ABST
    Figure CN119176727B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic metallization, and in particular to a method for preparing a metallized molybdenum-manganese paste. Molybdic acid, polymer microspheres, a surfactant and ammonia water are mixed, the pH value is adjusted to 1 and then the mixture is sealed for hydrothermal reaction. The obtained product is dried and subjected to a primary heat treatment at 350-450°C for 1-3 hours, then heated to 600-800°C for a secondary heat treatment for 5-10 hours, and finally subjected to a tertiary heat treatment at 1000-1100°C for 1-3 hours in a hydrogen atmosphere to obtain micro-nanometer hollow molybdenum powder. An activator, the hollow molybdenum powder and manganese monoxide are mixed and ball-milled, and then mixed with an organic binder to obtain the metallized molybdenum-manganese paste. The metallized layer obtained by the metallized molybdenum-manganese paste has high density and tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic metallization, in particular to a method for preparing a metallized molybdenum-manganese paste. Background Art

[0002] Ceramic-metal sealing is a key technology for vacuum devices, and its sealing quality directly affects the mechanical stability, insulation performance, vacuum sealing performance and environmental adaptability of vacuum devices.

[0003] Ceramic metal sealing includes many methods, such as molybdenum manganese method, active metal sealing, glass solder sealing, etc. The molybdenum manganese method ceramic metallization process has become the main ceramic metal sealing method at present because of its advantages such as simple operation, low economic cost and excellent sealing reliability. In the molybdenum manganese method ceramic metallization process, the key factors affecting the sealing strength and airtightness include the composition, uniformity and sintering process parameters of the metallization layer. With the improvement of industrial automation accuracy and the maturity of sintering technology, coating uniformity and sintering process are no longer the key factors restricting the performance of ceramic metallization. The influence of molybdenum manganese paste on sealing strength is particularly prominent. The metal film obtained by sintering the existing metallization molybdenum manganese paste has general bonding strength with the ceramic matrix material, and there are obvious limitations in many application fields. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for preparing a metallized molybdenum-manganese paste.

[0005] The technical solutions adopted are as follows:

[0006] A method for preparing a metallized molybdenum-manganese paste is as follows:

[0007] Molybdic acid, polymer microspheres, surfactant and ammonia water are mixed, the pH is adjusted to 1 and then sealed for hydrothermal reaction, the obtained product is dried and heat treated at 350-450°C for 1-3h, then heated to 600-800°C for 5-10h, and finally heat treated at 1000-1100°C for 1-3h in a hydrogen atmosphere to obtain micro-nano hollow molybdenum powder;

[0008] The metallized molybdenum-manganese paste is obtained by mixing an activator, hollow molybdenum powder and manganese monoxide, ball-milling the mixture and then mixing the mixture with an organic binder.

[0009] Furthermore, the polymer microspheres are any one of polyaniline nanospheres, polychloromethylstyrene nanospheres or polystyrene nanospheres.

[0010] Furthermore, the surfactant is a long-chain alkyl quaternary ammonium salt type surfactant.

[0011] Furthermore, the mass ratio of the molybdic acid, the polymer microspheres and the surfactant is 1:0.15-0.3:0.01-0.1.

[0012] Furthermore, the hydrothermal reaction temperature is 80-120° C., and the hydrothermal reaction time is 5-10 h.

[0013] Furthermore, the activator is CaO-SiO2-Al2O3-P2O5 glass powder.

[0014] Furthermore, the preparation method of the CaO-SiO2-Al2O3-P2O5 glass powder is as follows:

[0015] Mix CaCO3, SiO2, Al2O3 and NH4H2PO4, heat and melt them, then water-quench and ball-mill them to a particle size of less than 5 μm.

[0016] Furthermore, the mass ratio of CaCO3, SiO2, Al2O3, and NH4H2PO4 is 15-30:30-40:30-40:1-5.

[0017] Further, the organic binder includes terpineol and ethyl cellulose;

[0018] The mass ratio of terpineol to ethyl cellulose is 8-12:1.

[0019] Furthermore, in terms of mass percentage, the metallized molybdenum-manganese paste contains 10-20% activator, 10-15% manganese monoxide, 15-20% organic binder, and the remainder is hollow molybdenum powder.

[0020] Beneficial effects of the present invention:

[0021] The present invention provides a method for preparing a metallized molybdenum-manganese paste. Current studies have shown that the morphology, particle size and uniformity of molybdenum powder in the molybdenum-manganese paste have an important influence on subsequent processing. The hollow molybdenum powder prepared by the present invention can improve the density of the metallized layer, and the formed skeleton is more continuous and connected, has excellent conductive properties, is not easy to agglomerate during use, has a low shrinkage rate during the sintering process, and basically does not generate pores and pores, thereby improving the uniformity of the microstructure.

[0022] When preparing hollow molybdenum powder, polymer microspheres are used as sacrificial templates on the one hand, and can be directly carbon-thermally reduced after high-temperature carbonization to reduce the oxygen content. Since no chemical vapor migration occurs, the particle size and morphology of the product can be controlled. Long-chain alkyl quaternary ammonium salt surfactants can form micelles in the solution, and have the function of soft templates to promote the formation of pores. During sintering, the glass phase migrates into these pores under the action of capillary forces, thereby making the metallization layer and the ceramic closely bonded.

[0023] When preparing hollow molybdenum powder, ammonium molybdate generated by hydrothermal reaction during the first heat treatment is converted into molybdenum trioxide, and pyrolysis carbonization of polymer microspheres occurs during the second heat treatment. The second heat treatment is maintained for a long time, so that molybdenum trioxide and pyrolytic carbon undergo carbothermal reduction reaction. Since chemical vapor migration does not occur in this step, the particle size and morphology of the carbothermal reduction product can be controlled. Finally, hydrogen reduction is performed to convert all molybdenum oxides into elemental molybdenum, and a good particle size and morphology are maintained.

[0024] The glass phase formed by the melting of the activator has good wettability to the molybdenum powder, and its melting point and viscosity are lower than those of the glass phase in the ceramic body. Therefore, it first migrates to the interior, pores and ceramic body of the hollow molybdenum powder, and can fuse with a small amount of glass phase in the ceramic, reducing its melting point and viscosity, playing a driving and activating role, and promoting its migration to the gaps of the metallization layer. It is through the mutual migration of the glass phases on both sides that the ceramic and the metallization layer form a close and effective combination. The introduction of an appropriate amount of P2O5 in the activator plays a positive role in improving the tensile strength of the metallization layer. The reason may be that P2O5 reduces the glass transition temperature, promotes the formation of the glass phase, and improves the density of the metallization layer.

[0025] The metallized layer prepared by the metallized molybdenum-manganese paste of the invention has higher density and tensile strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 TEM image of the hollow molybdenum powder prepared in Example 1;

[0027] Figure 2 This is a SEM image of the interface of the metallization layer formed after the molybdenum-manganese paste is coated and sintered in Example 1. It can be seen that the bonding performance at the interface is good and no pores are seen. DETAILED DESCRIPTION

[0028] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0029] Embodiment 1:

[0030] This embodiment provides a method for preparing a metallized molybdenum-manganese paste:

[0031] 72g of molybdic acid, 12g of polystyrene nanospheres, 2g of surfactant CTAB and 400ml of 4mol / L ammonia water were mixed, ultrasonically vibrated for 30min, and the pH of the reaction solution was adjusted to 1 with 4mol / L hydrochloric acid solution. The reaction solution was sealed and heated to 120℃ for hydrothermal reaction for 8h. After returning to room temperature, the product was filtered. After drying, the product was heated to 400℃ at a rate of 5℃ / min for a first heat treatment for 2h, and then heated to 750℃ at a rate of 5℃ / min for a second heat treatment for 8h. Finally, the air was replaced with hydrogen, and the product was heated to 1050℃ at a rate of 5℃ / min for a third heat treatment for 2h. Micro-nano hollow molybdenum powder is mixed with CaCO3, SiO2, Al2O3, and NH4H2PO4 in a mass ratio of 20:40:30:2.5, heated to melt, and then water-quenched and ball-milled to a particle size of less than 5μm to obtain an activator. According to mass percentage, 12% of the activator, 58% of the hollow molybdenum powder, and 15% of manganese monoxide are mixed and ball-milled, and then evenly mixed with 15% of an organic binder composed of pine alcohol and ethyl cellulose in a mass ratio of 9:1 to obtain a metallized molybdenum-manganese paste.

[0032] Embodiment 2:

[0033] This embodiment provides a method for preparing a metallized molybdenum-manganese paste:

[0034] 72g of molybdic acid, 12g of polystyrene nanospheres, 2g of surfactant CTAB and 400ml of 4mol / L ammonia water were mixed, ultrasonically vibrated for 30min, and the pH of the reaction solution was adjusted to 1 with 4mol / L hydrochloric acid solution. The mixture was sealed and heated to 120℃ for hydrothermal reaction for 8h. After returning to room temperature, the mixture was filtered. The obtained product was dried and heated to 450℃ at a rate of 5℃ / min for 3h, then heated to 800℃ at a rate of 5℃ / min for 10h, and finally replaced the air with hydrogen and heated to 1100℃ at a rate of 5℃ / min for 3h to obtain Micro-nano hollow molybdenum powder is mixed with CaCO3, SiO2, Al2O3, and NH4H2PO4 in a mass ratio of 20:40:30:2.5, heated to melt, and then water-quenched and ball-milled to a particle size of less than 5μm to obtain an activator. According to mass percentage, 12% of the activator, 58% of the hollow molybdenum powder, and 15% of manganese monoxide are mixed and ball-milled, and then evenly mixed with 15% of an organic binder composed of pine alcohol and ethyl cellulose in a mass ratio of 9:1 to obtain a metallized molybdenum-manganese paste.

[0035] Embodiment 3:

[0036] This embodiment provides a method for preparing a metallized molybdenum-manganese paste:

[0037] 72g of molybdic acid, 12g of polystyrene nanospheres, 2g of surfactant CTAB and 400ml of 4mol / L ammonia water were mixed, ultrasonically vibrated for 30min, and the pH of the reaction solution was adjusted to 1 with 4mol / L hydrochloric acid solution. The reaction solution was sealed and heated to 120℃ for hydrothermal reaction for 8h. After returning to room temperature, the product was filtered. After drying, the product was heated to 350℃ at a rate of 5℃ / min for a first heat treatment for 3h, and then heated to 600℃ at a rate of 5℃ / min for a second heat treatment for 10h. Finally, the air was replaced with hydrogen, and the product was heated to 1000℃ at a rate of 5℃ / min for a third heat treatment for 2h. Hollow molybdenum powder to micro-nano level, CaCO3, SiO2, Al2O3, NH4H2PO4 in a mass ratio of 20:40:30:2.5 are mixed, and after heating and melting, water quenching and ball milling are carried out to a particle size of less than 5μm to obtain an activator. According to the mass percentage, 12% of the activator, 58% of the hollow molybdenum powder and 15% of manganese monoxide are mixed and ball milled, and then mixed evenly with 15% of an organic binder composed of pine alcohol and ethyl cellulose in a mass ratio of 9:1 to obtain a metallized molybdenum manganese paste.

[0038] Embodiment 4:

[0039] This embodiment provides a method for preparing a metallized molybdenum-manganese paste:

[0040] 72g of molybdic acid, 12g of polystyrene nanospheres, 2g of surfactant CTAB and 400ml of 4mol / L ammonia water were mixed, ultrasonically vibrated for 30min, and the pH of the reaction solution was adjusted to 1 with 4mol / L hydrochloric acid solution. The reaction solution was sealed and heated to 120℃ for hydrothermal reaction for 8h. After returning to room temperature, the product was filtered. After drying, the product was heated to 400℃ at a rate of 5℃ / min for a first heat treatment for 2h, and then heated to 750℃ at a rate of 5℃ / min for a second heat treatment for 8h. Finally, the air was replaced with hydrogen, and the product was heated to 1050℃ at a rate of 5℃ / min for a third heat treatment for 2h. Hollow molybdenum powder to micro-nano level, CaCO3, SiO2, Al2O3, NH4H2PO4 in a mass ratio of 20:40:30:5 are mixed, and after heating and melting, water quenching and ball milling are carried out to a particle size of less than 5μm to obtain an activator. According to the mass percentage, 12% of the activator, 58% of the hollow molybdenum powder and 15% of manganese monoxide are mixed and ball milled, and then mixed evenly with 15% of an organic binder composed of pine alcohol and ethyl cellulose in a mass ratio of 9:1 to obtain a metallized molybdenum manganese paste.

[0041] Embodiment 5:

[0042] This embodiment provides a method for preparing a metallized molybdenum-manganese paste:

[0043] 72g of molybdic acid, 12g of polystyrene nanospheres, 2g of surfactant CTAB and 400ml of 4mol / L ammonia water were mixed, ultrasonically vibrated for 30min, and the pH of the reaction solution was adjusted to 1 with 4mol / L hydrochloric acid solution. The reaction solution was sealed and heated to 120℃ for hydrothermal reaction for 8h. After returning to room temperature, the product was filtered. After drying, the product was heated to 400℃ at a rate of 5℃ / min for a first heat treatment for 2h, and then heated to 750℃ at a rate of 5℃ / min for a second heat treatment for 8h. Finally, the air was replaced with hydrogen, and the product was heated to 1050℃ at a rate of 5℃ / min for a third heat treatment for 2h. Hollow molybdenum powder to micro-nano level, CaCO3, SiO2, Al2O3, NH4H2PO4 in a mass ratio of 20:40:30:1 are mixed, and the mixture is heated to melt and then water-quenched and ball-milled to a particle size of less than 5μm to obtain an activator. According to the mass percentage, 12% of the activator, 58% of the hollow molybdenum powder and 15% of manganese monoxide are mixed and ball-milled, and then evenly mixed with 15% of an organic binder composed of pine alcohol and ethyl cellulose in a mass ratio of 9:1 to obtain a metallized molybdenum manganese paste.

[0044] Comparative Example 1: It is basically the same as Example 1, except that commercially available molybdenum powder (average particle size 1.5 μm, Sichuan Green Forest Technology Co., Ltd.) is used instead of the homemade hollow molybdenum powder.

[0045] Comparative Example 2: It is basically the same as Example 1, except that NH4H2PO4 is not added when preparing the activator.

[0046] Performance test: The metallized molybdenum manganese pastes in Examples 1-5 of the present invention and Comparative Examples 1-2 were respectively coated on 95 alumina ceramics by screen printing, and the coating thickness of the metallized layer was 60±5 μm. The samples were sintered at 1500°C for 60 min in a wet hydrogen atmosphere. The strength of the metallized layer of the prepared samples was tested according to SJ / T 3326-2016 "Test Method for Tensile Strength of Ceramic-Metal Seals", and the test results are shown in Table 1 below:

[0047] ;

[0048] It can be seen from Table 1 above that the metallized layer prepared by the metallized molybdenum-manganese paste of the present invention has a relatively high tensile strength;

[0049] By comparing Example 1 with Examples 4 and 5, it can be seen that too high or too low P2O5 content will cause a decrease in tensile strength;

[0050] By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the hollow molybdenum powder and the activator in the present invention play a positive role in improving the tensile strength of the metallized layer.

[0051] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a metallized molybdenum-manganese paste, characterized in that: The details are as follows: Molybdic acid, polymer microspheres, surfactant and ammonia water are mixed, the pH is adjusted to 1 and then sealed for hydrothermal reaction, the obtained product is dried and heat treated at 350-450°C for 1-3h, then heated to 600-800°C for 5-10h, and finally heat treated at 1000-1100°C for 1-3h in a hydrogen atmosphere to obtain micro-nano hollow molybdenum powder; The metallized molybdenum-manganese paste is obtained by mixing an activator, hollow molybdenum powder and manganese monoxide, ball-milling the mixture and then mixing the mixture with an organic binder; The activator is CaO-SiO2-Al2O3-P2O5 glass powder; The preparation method of the CaO-SiO2-Al2O3-P2O5 glass powder is as follows: Mix CaCO3, SiO2, Al2O3 and NH4H2PO4, heat and melt, then water quench and ball mill to a particle size of less than 5μm; The mass ratio of CaCO3, SiO2, Al2O3, and NH4H2PO4 is 15-30:30-40:30-40:1-5; The polymer microspheres are any one of polyaniline nanospheres, polychloromethylstyrene nanospheres or polystyrene nanospheres; The surfactant is a long-chain alkyl quaternary ammonium salt surfactant; The mass ratio of molybdic acid, polymer microspheres and surfactant is 1:0.15-0.3:0.01-0.1; The hydrothermal reaction temperature is 80-120°C, and the hydrothermal reaction time is 5-10h.

2. The method for preparing the metallized molybdenum-manganese paste according to claim 1, wherein: The organic binder includes terpineol and ethyl cellulose; The mass ratio of terpineol to ethyl cellulose is 8-12:

1.

3. The method for preparing the metallized molybdenum-manganese paste according to claim 1, wherein: According to mass percentage, the metallized molybdenum-manganese paste contains 10-20% activator, 10-15% manganese monoxide, 15-20% organic binder, and the remainder is hollow molybdenum powder.

Citation Information

Patent Citations

  • Molybdenum powder for ceramic metallizing and preparing method of molybdenum powder

    CN103801706A

  • Metallization sintering powder for 95 alumina ceramic middle temperate metallization paste and preparation method thereof

    CN103951468A